Cultivo in vitro e aclimatização de Epidendrum cinnabarinum Salzm. ex Lindl. (Orchidaceae) uma espécie com integridade genética ameaçada: uma estratégia para conservação - Santos, Lucinalva Azevedo dos (2016)
The target species of this study, Epidendrum cinnabarinum Salzm, besides having high ornamental potential, has a disjunct distribution between rocky outcrops in Northeast region, with small populations characterized by large interpopulation genetic differences, which makes the specie genetic integrity being threatened. In vitro cultivation techniques propitiate to obtain a large quantity of seedlings in limited time and space, being able to be used in resettlement projects of the specie or for commercial purposes. Among the components of the culture media, sucrose is a very important component in the culture medium in vitro that serves as a source of carbon and energy. In our study we used the medium 1 / 2MS with five different concentrations of sucrose: 0,0g.L-1; 10,0g.L-1; 20,0g.L-1; 30,0g.L-1 and 40,0g.L-1 sucrose. After 10 days of inoculation and germination it was evaluated, and over 80 days, it was evaluated the leaf primordium formation in protocorm; over 270 days of inoculation were evaluated: number of leaves, numbers of roots, bigger root length, shoot length, stem diameter, number of seedlings and total number of protocorms. For acclimatization seedlings originated in vitro development in these sucrose concentrations, they were transplanted to pots containing vermiculite and sphagnum moss in the ratio 1: 1, comprising five treatments with five replications, and ten seedlings in each individual plot. Over 45 days of acclimatization, the plants were evaluated for survival rate, number of leaves, numbers of roots, bigger root length, shoot length, stem diameter and larger sheet length. There was no germination at a concentration of 0,0g.L-1 sucrose. The remaining sucrose concentrations showed germination and formation of leaf primordia. The concentration of 40,0g.L-1 sucrose showed the best results for the majority of variables, in addition to promote better acclimatization in seedlings of E. cinnabarinum. It was concluded that the in vitro and ex vitro development of E. cinnabarinum was strongly and positively influenced by the concentration of sucrose in the culture medium for all variables with better results at concentrations of 30,0g.L-1 and 40, 0g.L-1 sucrose.